Women$1 (Bs experiences of homelessness: a longitudinal study s - Bretherton, J. (Social Policy and Society)
Drawing on the results of a qualitative longitudinal analysis of the experiences of homeless people using an employment related programme in the UK, this article explores the experiences of homeless women. Research focused on women$1 (Bs trajectories through homelessness remains unusual and this comparatively large study provided an opportunity to look at a group of homeless women over time. The results from 136 in-depth interviews with forty-seven homeless women are reported. The interviews explored their lives prior to becoming homeless, their routes into homelessness and their trajectories through and out of homelessness. The article does not compare experiences across gender, focusing solely on women, because the existing evidence base focuses largely on the experiences of lone homeless men. The goals of the article are twofold, first to add to the existing evidence on women$1 (Bs experiences of homelessness and second to add to emergent debates on whether gender is associated with differentiated trajectories through homelessness.- Reproduceds
Keywords: Homelessness, Homeless, Women, Longitudinal, Trajectories